The wild bunch [videorecording (Blu-Ray)] - Holden, William, 1918-1981; Borgnine, Ernest, 1917-2012; Ryan, Robert, 1909-1973; O'Brien, Edmond, 1915-1985; Oates, Warren, 1928-1982; Sánchez, Jaime, 1938-; Johnson, Ben, 1918-1996; Fernández, Emilio, 1904-1986; Martin, Strother, 1919-1980; Jones, L. Q., 1927-2022; Peckinpah, Sam, 1925-1984; Feldman, Phil, 1922-1991; et al. (Warner Home Video, 2007)
Outlaws on the U.S.-Mexican border face the march of progress, the Mexican army and a gang of bounty hunters led by a former member as they plan to rob a U.S. Army train.